1992
DOI: 10.1128/mcb.12.9.3930
|View full text |Cite
|
Sign up to set email alerts
|

A new member of the protein kinase C family, nPKC theta, predominantly expressed in skeletal muscle.

Abstract: A new protein kinase C (PKC)-related cDNA with unique tissue distribution has been isolated and characterized. This cDNA encodes a protein, nPKCO, which consists of 707 amino acid residues and showed the highest sequence similarity to nPKC8 (67.0% in total). nPKCO has a zinc-finger-like cysteine-rich sequence (Cl region) and a protein kinase domain sequence (C3 region), both of which are common in all PKC family members. However, nPKCO lacks a putative Ca2+ binding region (C2 region) that is seen only in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(195 citation statements)
references
References 59 publications
7
187
1
Order By: Relevance
“…Hybridization was performed as described previously (Osada et al, 1992). The ®lters were ®nally washed with 0.16SSC (16SSC=150 mM NaCl, 15 mM sodium citrate, pH 7.0) containing 0.1% SDS for 30 min at 658C.…”
Section: Screening Of Cdna Libraries and Dna Sequencingmentioning
confidence: 99%
See 3 more Smart Citations
“…Hybridization was performed as described previously (Osada et al, 1992). The ®lters were ®nally washed with 0.16SSC (16SSC=150 mM NaCl, 15 mM sodium citrate, pH 7.0) containing 0.1% SDS for 30 min at 658C.…”
Section: Screening Of Cdna Libraries and Dna Sequencingmentioning
confidence: 99%
“…RNA electrophoresis, blotting onto a nylon membrane, and hybridization were performed as described before (Osada et al, 1992). The mouse cDNA fragment (719 bp) from clone 403 was used as a hybridization probe.…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, PKC was described as a Ca 2+-and phospholipid-dependent serine/threonine kinase [4,5], and later it was shown to be the major intracellular receptor for the tumorpromoting phorbol esters [6,7]. cDNA cloning and careful examination of the encoded proteins has revealed that the members of the PKC family can be classified into three major groups, namely, classical, cPKCs-c~, -/31, -1~II and -y, [8]; novel, nPKCs-~, -e, -/7, -0, and -¢t [9][10][11][12][13][14][15]; and atypical, aPKCs -5 and -t (the human counterpart of mouse aPKC-2) [10,1618]. Only the cPKCs require Ca 2+ for activity.…”
Section: Introductionmentioning
confidence: 99%